An analysis on the effect of the three-incision combined approach for complex fracture of tibial plateau involving the posterolateral tibial plateau - Guqi Hong; Xiaowen Huang; Tianrun Lv; Xiang Li (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background The clinical effect of the three-incision combined approach for complex fracture of tibial plateau involving the posterior tibial plateau was discussed. Methods A retrospective analysis was performed for 13 cases receiving surgery for complex fracture of tibial plateau from July 2015 to June 2019. They received surgery via the three-incision combined approach, and regular postoperative reexamination was performed at the outpatient clinic. During the last follow-up, Hospital for Special Surgery (HSS) Knee Scoring System was used to assess the knee joint function; the Lysholm score was used to assess the knee mobility. The anterior, posterior, and rotational stabilities of the knee joint were assessed by the Lachman test and pivot-shift test. Results There was no nonunion and delayed union, implant loosening and fracture, or refracture, and neither were there neurological symptoms or restricted mobility in daily life. During the follow-up, none of the cases were found with restriction of knee mobility caused by internal fixation or apparent pain. The HSS score during the last follow-up was 86–100 (average, 90.2 ± 6.8), and the excellent and good rate was 100%; the Lysholm score was 86–100 (average, 95.7 ± 2.6). All cases were negative for the Lachman test and pivot-shift test. The knee flexion mobility was 100~140° (average, 127.2° ± 11.4°). Postoperative X-ray indicated anatomical reduction of bone fractures in all cases. Loss of reduction or loosening and fracture of internal fixation was not observed by postoperative regular reexaminations. The posterior tibial slope at 6 months after surgery was 6~16° (average, 10.66 ± 2.58°), the varus angle was 84~89° (average, 86.52 ± 1.46°), the Rasmussen radiological score was 12~18 (average, 16.12 ± 1.35), and the excellent and good rate was 100%. Conclusion The three-incision combined approach proved safe and reliable for complex fracture of tibial plateau involving the posterior tibial plateau and is worthy of further popularization.